Recovery of phosphates from anaerobic MBR effluent using columns of eggshell and seagrass residues and their final use as a fertilizer - Photiou, Panagiota; Poulizou, Maria; Vyrides, Ioannis (My University, 2023)
The combination of a submerged anaerobic membrane bioreactor (SAnMBR) and two biowaste adsorption columns (eggshell (EGSL) and seagrass (SG)) was studied for the first time to evaluate the recovery of phosphates from wastewater. Reject wastewater from anaerobic sludge dewatering process was fed into the SAnMBR and the results showed a COD removal of 50%. The phosphate removal efficiency was low and as such, the effluent from SAnMBR was then passed through two columns containing thermally treated eggshell and seagrass residues for further phosphate removal. The final effluent analysis confirmed that phosphates could be additionally removed resulting in over 95% recovery (flow rate 0.3 L d−1), for both biowaste materials. The ammonium and COD removal after the adsorption columns was low, indicating the high selectivity towards phosphates. Moreover, the solid residues after adsorption were evaluated as soil conditioners on Lepidium sativum and Sinapis alba seeds. The SG end product exhibited high GI values for both seeds tested indicating a positive effect on plant growth, while the EGSL end product negatively affected the seed germination. The fractionation analysis of phosphorus showed that inorganically bound phosphorus (IP) was the major phosphorus fraction in EGSL and SG end product, accounting for 92.6 and 95.7% of TP, respectively. The results of this study suggest that the SG and EGSL could be effectively reclaimed as selective adsorbents towards phosphates in combination with a SAnMBR and the SG solid residues after adsorption can be directly applied for agricultural purposes, contributing to the development of a zero-waste technology.
Keywords: Columns; Phosphate recovery; SAnMBR effluent; Sludge dewatering